Assessment of Analgesic, Cytotoxic and Antioxidant activities of Vallaris solanacea (Roth) Kuntze - Karmakar, Utpal Kumar; Ghosh, Dyuti; Sadhu, Samir Kumar (Stamford Journal of Pharmaceutical Sciences, 2011)
The ethanolic extract of leaves and stem of Vallaris solanacea (Roth) Kuntze (Family: Apocynaceae) was screened for its analgesic, cytotoxic and antioxidant activities. Phytochemical analysis of the extract indicated the presence of Reducing Sugar, Tannins, Saponins, Gums, Steroids, Alkaloids, and Glycosides. The ethanolic extract showed statistically significant analgesic activity (p<0.005) in acetic acid induced writhing inhibition in mice at the dose of 500mg/kg body weight and also showed mild effect at the doses of 250mg/kg body weight. In the brine shrimp lethality test, the extract showed cytotoxicity with LC50 80 μg/ml and LC90 320 μg/ml. In the qualitative antioxi-dant assay using DPPH (1, 1-diphenyl-2-picryl hydrazyl) the extract showed free radical scavenging properties. These primary findings suggest that the extract might possess some chemical constituents that are responsible for analgesic, cytotoxic and antioxidant activities. Key words: Vallaris solanacea (Roth) Kuntze; phytochemical study; analgesic activity; cytotoxic activity; antioxi-dant activity. DOI: http://dx.doi.org/10.3329/sjps.v4i1.8869 SJPS 2011; 4(1): 64-68